Ali Shariati’s Reading of Ibn Khaldun - Seyed Javad Miri Meynagh (İnsan & Toplum)
Ali Shariati has written extensively on various aspects of social theory and the history of religions, but very few have studied his views on Ibn Khaldun. In other words, my main concern in this article is focused squarely on Shariati's reading of Ibn Khaldun's discourses. My argument is not to be preoccupied by Eastern or WesternKhaldunian studies or even how sociologists and social anthropologists such as Ahmad Ashraf construe him. On the contrary, I attempt to go through the 36 volumes of Ali Shariati's legacy in this article, delving into his reections on Ibn Khaldun. Does he say anything substantial at all on Ibn Khaldun? What does Shariati think of Ibn Khaldun? How does Shariati read Ibn Khaldun? Has anybody else worked upon the typeof Ibn Khaldun thatShariati has construed? As muchas I have studied the literature in the Persian, English, Swedish, Russian, Arabic, and Turkish languages, no references are found regarding Shariatia’s interpretations of Ibn Khaldun. But, as Ali Shariati is one of the most pivotal contemporary non-Eurocentric social theorists in the world and his views on one of the most important classical social thinkers (i.e., Ibn Khaldun) should not go unheeded,this is why I have taken upon this challenge and inquired upon the question that is begged of what Shariati's approach towardIbn Khaldun is.